Adaptation Planning: An Integrated Approach to Understanding Vulnerability in the Lake Victoria Basin - Petty, Celia; Ngoleka, Stella; Cornforth, Rosalind; Achiro, Eunice; Acidri, James; Ainslie, Andrew; Owuor, John; Walker, Grady (Frontiers in Climate, 2022)
Decision makers need actionable information on the factors that inhibit household adaptation to climate variability and other changes, especially those changes reinforcing environmentally unsustainable livelihood strategies. In this paper, we show how a combination of quantitative and qualitative data can help assess current livelihood vulnerability and the social and institutional obstacles facing specific population groups. Detailed analysis of current household economies in two case study communities (one in Uganda and one in Kenya) in the Lake Victoria Basin, East Africa, was combined with a qualitative, intersectional exploration of constraints on income adaptation and diversification. Quantitative household economy analysis showed low levels of household disposable income overall and additionally, poor returns on investment from enterprises typically controlled by women. Qualitative research highlighted changes in gender roles driven by women’s entrepreneurial responses to reduced household income from traditional agricultural and natural resource-based activities. However, due to unequal access to finance and culturally mediated norms and expectations, many women’s enterprises were small scale and insecure. The broader political economy context is one of limited national investment in education and infrastructure, further constraining local opportunities for human and economic development. The approach described here was directed by the need to understand and quantify economic vulnerability, along with the cultural and institutional constraints on adaptation, as a basis for making better adaptation policies and interventions.